A Philosophical Defence of Mainstream Economic Theory (Culturas Científicas, 2025)
This paper will be a defence of mainstream economics. I will take the criticisms of Muñoz Ferrer (2021), who tries to show the dangers of market economics by criticising mainstream economic theory. Muñoz Ferrer's criticisms will allow me to point out some commonly misunderstood aspects of mainstream economic theory that are based on a misunderstanding of the development of economic thought, which leads to a misconception of what mainstream economics is about and its scope. I will begin with a brief history of the discipline, starting with the marginalist revolution, the origin of "subjectivity understood as the mere pursuit of individual interest" (ibid., p.66), or a false psychology as Muñoz Ferrer also calls it. I will then explain how, from the ordinalist revolution onwards, economics begins to separate from psychology. This will allow me to show that positions, such as Muñoz Ferrer's, falsely presuppose that economics seeks to be some kind of psychology. Finally, my argument will show the epistemic value of models in economics and that, even within the very practice of economists, there are not the problems that their critics attribute to them.
Keywords: Philosophy of Economics; Market economy; Orthodox economics; Utility Theory.